United Kingdom : 2000 Article IV Consultation-Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Authorities of the United Kingdom. (IMF Staff Country Reports; Country Report ;, 2001)
Strengthened macroeconomic and structural policies, underpinned by improved monetary and fiscal policy frameworks, have contributed to the United Kingdom's achievements. Executive Directors commended these developments, and supported the focus of policies to encourage innovation and entrepreneurship, promote research and development, and strengthen the competition in view of the need to foster the New Economy and boost productivity growth in the rest of the economy. They agreed that the banking system is profitable and well capitalized, but stressed the need to be more vigilant.